Earnings Management in Retail Industry: Indonesian Listed Firms - Tristany, Chelsie (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2020)
Agency problem encourages the use of contracts to mitigate the conflict of interest between investors and managers. The use of reward contract incite discretionary actions from the managers’ side and as a result, earnings management is applied through various forces. This paper aims to reveal the firm attributes that may influence the motivation of managers to manage earnings in Indonesian retail listed companies during 2017 to 2019. The independent variables employed are firm size, leverage and profitability with firm size, debt to equity ratio, and return on assets as the proxies respectively. The dependent variable is earnings management with discretionary accruals measure using modified Jones model (1995) as the proxy. The result indicates that the three variables simultaneously affect earnings management significantly. However, individually, the only variable that has a significant effect on earnings management is profitability. The result reveals that both firm size and leverage are considered as insignificant characteristics in the study of earnings management. It indicates that size of firm or the amount of debt financing does not significantly affect manager’s decision in employing earnings management. However, profitability has a significant effect due to the frequent use as a target in reward contracts to measure the effort of managers in maximizing the wealth of shareholders and determinant in the bonus or compensation the managers would receive.ReferencesAlareeni, B. (2018). The impact of firm-specific characteristics on EM: evidence from GCC countries . International Journal of Managerial and Financial Accounting, 1-20.Azhari, A. (2018, July 24). Learn for Finance. Retrieved from THE CLASSIC ASSUMPTION TEST (AUTOCORRELATION, HETEROSCEDASTICITIY, MULTICOLINERITY AND NORMALITY) FOR PANEL DATA (WITH SPSS, EVIEWS AND STATA): http://learnforfinance.blogspot.com/Bassiouny, S. W. (2016). The impact of firm characteristics on EM: an empirical study on the listed firms in Egypt . Journal of Business and Retail Management Research (JBRMR) , 34-45.Berman, B., Evans, J. R., & Chatterjee, P. (2018). Retail Management: A Strategic Approach 13th Edition. Harlow: Pearson Education Limited.Bragg, S. (2020, June 9). AccountingTools. Retrieved from Wealth maximization: https://www.accountingtools.com/articles/what-is-wealth-maximizationDiri, M. E. (2018). Introduction to EM. Gewerbestrasse : Springer International Publishing .Ghani, E. K., Azemi, N. A., & Puspitasari, E. (2019). The Effect of Firm Characteristics on EM Practices among Malaysian Public Listed Companies in the Technological Industry . MANAGEMENT & ACCOUNTING REVIEW, 41-55.Gunawan, I. K., Darmawan, N. A., & Purnamawati, I. G. (2015). PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) . Jurusan Akuntansi Program S1 .Hargrave, M. (2020, April 12). Investopedia. Retrieved from Return on Assets—ROA: https://www.investopedia.com/Hayes, A. (2020, July 2). Investopedia. Retrieved from Leverage: https://www.investopedia.com/terms/l/leverage.aspHayes, A. (2020, April 27). Investopedia. Retrieved from Debt-To-Equity Ratio – D/E: https://www.investopedia.com/Horton, M. (2019, March 31). Investopedia. Retrieved from The Difference Between Profitability and Profit: https://www.investopedia.com/Jaya, I. M., & Narsa, I. M. (2020). The Beauty and the Beast of Earning Management in Indonesia . Opción, 1097-1140 .Kamel, H. (2012). EM and initial public offerings: a new perspective from Egypt . Journal of Accounting in Emerging Economies , 96-118 .Kiisel, T. (n.d.). ondeck. Retrieved from Maximizing The Value of Financing for Retail Businesses: https://www.ondeck.com/resources/financing-retail-businessesLin, W., & Rong, M. (2012). Impacts of other comprehensive income disclosure on EM . Nankai Business Review International , 93-101 .Maheshwari, Y., & Agrawal, K. (2015). Impact of IPO grading on EM . Journal of Financial Reporting and Accounting , 142-158 .Opportunity Business Loans. (n.d.). Retrieved from Financing Options for Your Retail Business: https://oppbusinessloans.com/financing-options-for-your-retail-business/Riadi, M. (2020, April 24). Kajian Pustaka. Retrieved from Ukuran Perusahaan (Pengertian, Jenis, Kriteria dan Indikator): https://www.kajianpustaka.comRoss, S. (2020, January 9). Investopedia. Retrieved from What Is a Good Profit Margin for Retailers?: https://www.investopedia.com/Roudaki, J. (2016). EM in Developing Countries: Iranian Listed Companies . Journal of Accounting – Business & Management (JABM), 14-32 .Soliha, E. (2008). ANALISIS INDUSTRI RITEL DI INDONESIA . Jurnal Bisnis dan Ekonomi (JBE), 128-142.Suhardianto, N., & Harymawan, I. (2011). A DECADE OF EM RESEARCHES IN INDONESIA . Asia Pacific Journal of Accounting and Finance , 90-119.Swai, J. P. (2016). The Impact of Corporate Governance and Firm-Specific Characteristics on EM: Evidence from East Africa . Research Journal of Finance and Accounting , 139-156.Uwuigbe, U., Uwuigbe, O. R., & Bernard, O. (2015). ASSESSMENT OF THE EFFECTS OF FIRMS’ CHARACTERISTICS ON EM OF LISTED FIRMS IN NIGERIA . Asian Economic and Financial Review, 218-228.Waweru, N. M., & Riro, G. K. (2013). Corporate Governance, Firm Characteristics and EM in an Emerging Economy . JAMAR, 43-64.Stephanie G. (2020). StatisticsHowTo.com: Elementary Statistics for the rest of us! Retrieved from Coefficient of Determination (R Squared): Definition, Calculation: https://www.statisticshowto.com/probability-and-statistics/coefficient-of-determination-r-squared/Stephanie G. (2020). StatisticsHowTo.com: Elementary Statistics for the rest of us!  Retrieved from Hypothesis Testing: https://www.statisticshowto.com/probability-and-statistics/hypothesis-testing/